Feasibility Study of Microhydro Power Plant on Kalimaja River In Dusun Kedondong Rame Ruguk Village Ketapang District Lampung South - Syaikhurrohman Syaikhurrohman (International Conference on Engineering and Technology Development (ICETD), 2017)
Electricity is one of the primary needs of human life that needed an efficient power plant. Power microhydro (MHP) is an alternative source of electrical energy for the community. MHP provides many advantages, especially for rural communities throughout Indonesia. While other energy thinning and a negative impact, then the water becomes a very important energy source because it can be used as a source of cheap energy power plants and does not cause pollution.This study aims to provide information to the Community, especially Hamlet KedondongRame that the availability of the potential provided by nature can be used as a source of electric power. This research was conducted by analyzing the feasibility of the River Kalimaja as micro hydro power plant which includes the water flow, the height waterfall and accuracy in the use of turbine type.Selection of the type of turbine used is influenced by the high discharge and falling water. Based on data collection in the field and based on the importance of the minimum flow of0.0610 / s and head 21.96 meters effectiveand specific speed 65.95 rpm, the turbine used in the design of the planning study isturbineCross-Flowtype